Electrochemical Analysis of Azadirachta indica Leaves as a Corrosion inhibitor on Mild Steel in 1 M H2SO4 - Cyril OCHERI; Victor S. AIGBODION; Esther O. AMEH; Ihebuchuwu C. EZEAKU; Chibuikem A. OKAFOR; Uchenna C. AMAZUE; Eddy R. OMONIGHO (FUDMA Journal of Engineering and Technology, 2025)
Corrosion inhibition of mild steel in acidic environments is vital in several industrial applications. This study was based of the electrochemical analysis of Azadirachta indica Leaf Extract(ALE) as corrosion inhibitor on mild steel in 1mol. H2SO4. The Electrochemical analysis is a technique was used to study the chemical properties and reactions of substance by measuring the flow of electrical current or potential difference This process was used to determine the ions in the leaf extract and to understand the oxidation-reduction reactions and the kinetics presence in the leaf extract. . The Fourier Transform Infrared Spectroscopy (FTIR) was used to determine the functional groups present. The phytochemical analysis was used to identify and quantify the bioactive compounds that were present in the leaf extract. The chemical composition of the mild steel material was determined . The pH meter was used to determine the level of acidicity on the extract. The Scanning Electron Microscopy (SEM and Energy Dispersive Spectroscopy were used to determine the morphology and the elemental weight (%) of the mild steel . The results of the corrosion test using the Electrochemical analytical technique revealed the stability of the oxide with respect to time(sec). The potentiodynamic polarization indicates that the corrosion rate decreases with respect inhibition addition thereby mitigating the corrosion process. The result of the EIS revealed that the addition of the extract increased the diameter of the semicircle in the Nyquist plot, indicating a decrease in corrosion rate. The Bode plot revealed an increase in impedance value at high frequencies, indicating a decrease in corrosion rate. The results from FT-IR identified several key components that created a protective thin film layer that stopped the release of hydrogen ions (H+) in the presence of acid, including C-C stretching, aromatic compounds, N-H2 symmetric stretching vibration, N-H symmetric stretching, and others. The functional groups identified by FTIR analysis of the protective film formed by leaf extract in H2SO4 .The hydroxyl (OH) groups, carbonyl (C=O) groups , the amines (N-H) groups and aromatic (C=C) groups, these groups possesses corrosion inhibition properties by coordinating with metal ions or forming stable complexes with the metal surface. The XRD results revealed sharp peaks indicate crystalline structure of the mild steel indicating the presence of corresponding compounds such as Fe(MgSO4), FeS2, CaCO3, and Fe2O3. The SEM / EDX revealed the morphology that exhibit smooth an uniform structures indicating the presence of inhibition while the EDX shows the elements in weight(%) The Phytochemical analysis shows the presence of Alkaloids 0.6%, Flavonoids 5.8%, Saponins 1.5%, tannins 3.6% and Phenol 7.8%. The pH values obtained indicated that Azadirachta leaf extract has 1.0 while 1M H2SO4 contains 0.5.The findings of potentiodynamic polarisation demonstrated that the corrosion rate dropped from 1.164e+002 to 1.3166e+004 in the 0.7g of 30mL in 1M H2SO4 medium and from 1.164e+002 to 1.042e+004 in the 0.9g of 30mL in H2SO4. The development of a physical protective layer in the mild steel was credited with the enhanced corrosion resistance of the Azadirachta indica leaf extract. The extract’s chemical inertness was also cited as a factor in the mild steel’s lower rate of corrosion. The findings show that Azadirachta indica leaf extract is environmentally friendly on the mild steel which serves as corrosion inhibitor in acidic settings. The results revealed that the extract has good corrosion inhibitory properties that can mitigate the corrosion process.